FLUCTUATION OF INFLATION VALUE AND BI RATE AGAINSTVOLATILITY OF STOCK PRICE IN PT. UNILEVER INDONESIA Tbk - Nely Supeni; Helmi Agus Salim (STIE Mandala Jember, 2020)
PT. Unilever Indonesia Tbkis one of the companies in the Consumer Goods Industry sector on the Indonesia Stock Exchange (BEI) with the highest share value throughout 2018. The purpose of this study is 1) To partially determine the effect of inflation and the BI Rate on Stock PriceVolatility at PT . Unilever Indonesia Tbk, 2) To find out the effect of simultaneous Inflation and BI Rate on Stock Price Volatility at PT. Unilever Indonesia Tbk.This type of research is quantitative research with secondary data type then the analysis used is Multiple Linear Regression. The results of the analysis state that partially Inflation has a significant negative effect on Stock Price Volatility while the BI Rate has a significant negative effect on Stock Price Volatility. Then the results of thesimultaneous analysis state that inflation and the BI Rate have a significant effect on stock price volatility. Keywords:Inflation, BI Rate, Stock Price Volatility